The Influence of the Heutagogy Approach Based on Xmind Mapping on the Critical Thinking Skills of Class X Students at SMA Negeri 5, Barru Regency - Rika, Rika; Adam, Andi; Ayu, Sadriana (DIDAKTIKA, 2025)
This study aims to examine the effectiveness of the Heutagogy approach based on Xmind Mapping in improving students' critical thinking skills in history subjects at SMA Negeri 5 Barru Regency. The research employed a one-group pretest-posttest design involving 70 tenth-grade students selected through cluster random sampling. The instruments used in this study were essay tests and observation sheets. The findings revealed a significant increase in the students’ average scores, from 31.92 in the pretest to 66.45 in the posttest. The Mann-Whitney statistical test showed a significance value of 0.000 (<0.05), indicating that the approach had a significant effect on enhancing students’ critical thinking abilities. Therefore, the Heutagogy approach integrated with Xmind Mapping can be considered an effective strategy to improve the quality of history learning and foster students’ critical thinking skills.Keywords: Heutagogy, Xmind Mapping, Critical Thinking, History Learning, Senior High School